Characterization and taxonomic evaluation of landraces of capsicum spp. in Kerala - Asish I Edakkalathur (Department of Plant Breeding and Genetics, College of Horticulture, 2018)
Capsicum is a unique genus coming under the family Solanaceae. This genus includes nearly 40 species among which five viz. C. annuum, C.chinense, C. frutescens, C. baccatum and C. pubescens are cultivated. Large number of types, the transitory nature of these types, introgressive hybridization and environmental influence make species arrangement in Capsicum a confusing task. Even though Kerala is rich in the diversity of Capsicum, a comprehensive study of landraces available has not yet been carried out. In this background, the present project was carried out with the objective of characterizing the landraces of Capsicum species in Kerala using morphological markers and validating the key for the identification of different taxa using molecular and biochemical markers. Ripened fruit samples of 262 accessions were collected from the different districts of Kerala during December, 2013 to August, 2014. These accessions were planted in augmented block design along with released varieties from Kerala Agricultural University as checks at National Bureau of Plant Genetic Resources, Regional Station, Thrissur. Morphological characterization was done by considering both qualitative and quantitative characters. Numerical Taxonomy and Multivariate Analysis System (NTSYS) software version 2.10 z was used for construction of phenogram based on forty four qualitative characters available in the Capsicum descriptor (IPGRI, 1995). Accessions belonging to three species viz., C. annuum, C.chinense and C. frutescens formed species specific clusters. C. baccatum accessions clustered with C. frutescens. C. chinense accessions were clearly separated and distantly placed from C. annuum accessions revealing genetic dissimilarity between the above two species.. Out of 42 clusters formed at 70 per cent similarity level, 39 are mono-specific clusters. Morphological characterization based on